A novel compact CPW Band-stop filter using O-DGS configuration - Elmahjouby Sghir; Ahmed Errkik; Jamal Zbitou; Larbi El abdellaoui; Abdelali Tajmouati; Mohamed Latrach (Institute of Advanced Engineering and Science, 2019)
A novel and compact multi-band stop filter using two different structures of circular DGS and circular DGS loaded with O-DGS unit, has good selectivity and wide upper pass band performance with good rejection based on defected ground structure (DGS) integrating a circular ring resonator to suppress undesired spurious bands frequency or harmonics in radio frequency and microwave circuits is proposed. An equivalent circuit model has been derived for the both structures of circular DGS and circular DGS loaded. The presented filter has a compact size because the circular ring resonator is integrated in DGS, the both of them are etching in the ground plane. The proposed filter presents an optimization method for generating multi-band characteristics without using a periodic cells or other complicate topology. The simulated results by ADS Agilent are presented and compared with the results simulated by two others software: CST and HFSS. Good agreement between the three simulated results is observed.